Mapping the research trends on blockchain technology in food and agriculture industry: A bibliometric analysis - Niknejad N.; Ismail W.; Bahari M.; Hendradi R.; Salleh A.Z. (Elsevier B.V., 2024)
Indexed by WOS/Scopus/ERA